Analisis Penggunaan Hipnosis Forensik Sebagai Metode Komplementer Pembuktian Tindak Pidana Pada Pemeriksaan Saksi Dalam Proses Penyidikan - Mohamad Aldi Djafar; Robby W. Amu; Marten Bunga (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
To find out and analyze the use of forensic hypnosis as a method of examining witnesses in proving criminal acts in other countries. To find out and analyze the use of forensic hypnosis as a method of examining witnesses in the perspective of proof of criminal acts at the investigative level in IndonesiaThe type of research used is normative juridical. The focus of the normative approach is to find, analyze and then formulate norms for the use of hypnosis. While the focus of the juridical approach is to explain the use of forensic hypnosis in several countries by referring to legal concepts or expert opinions, legal principles or principles and legal sources that apply universally.Whereas forensic hypnosis has been used as a method of examining witnesses in the investigative process in the United States, Canada and Hong Kong where information from the results of forensic hypnosis is used by investigators to search for, collect evidence and strengthen evidence. Meanwhile, de jure court decisions in each country that recognize the use of forensic hypnosis is a source of jurisprudence and legal legitimacy for applying forensic hypnosis as a method of examining witnesses in proving criminal offenses at the investigative level in Indonesia. Whereas the use of forensic hypnosis as a method of examining witnesses in the perspective of proving a crime at the level of investigation in Indonesia is no different from the method of examining witnesses in the investigation process in general. As a complementary method, it consists of 4 (four) stages namely pre-induction, induction, suggestion and termination where implicitly the use of forensic hypnosis as a method of examining witnesses in the investigation process is a manifestation of the investigator's enthusiasm in carrying out other actions according to law.In order to further strengthen and optimize the existence of the use of forensic hypnosis as a method of examining witnesses in the investigative process in Indonesia, it is hoped that the legislature will provide confirmation on the use of forensic hypnosis which must be contained in statutory regulations or in standard procedures.